Language errors in writing skills according to Corder’s theory - Ignacy, Richard; Subramaniam, Vijayaletchumy (Human Resources Management Academic Research Society (HRMARS), 2024)
Linguistic errors in the Malay Language, including morphological and syntactic elements, often occur in essay writing. This study focuses on the forms of language errors identified from morphological and syntactic aspects. A qualitative approach involving document analysis (written essays), observations, and interviews was implemented with 120 secondary school students in the Kerian district of Perak. Based on Corder's Theory (1974), language errors from morphological aspects in word groups such as nouns, verbs, DM laws and noun phrases were found. Similarly, syntactic errors, including code mixing, inaccurate discourse markers, unbalanced paragraphing, compound sentence mistakes, and abbreviations, were identified. Collectively, these language errors have impacted the writing quality in the Malay Language among Form Four students. Efforts should be made to overcome these language errors to enhance writing quality. This can improve student outcomes, increase educators' awareness of common errors in essays, and uphold the dignity of the Malay language